COLREGs-Compliant Path Planning for Autonomous Surface Vehicles: A Multiobjective Optimization Approach*. Issue 1 (July 2017) - Hu, Liang; Naeem, Wasif; Rajabally, Eshan; Watson, Graham; Mills, Terry; Bhuiyan, Zakirul; Salter, Ivor
Abstract: In this paper, a multiobjective optimization framework is proposed for on-line path planning of autonomous surface vehicles (ASVs), where both collision avoidance and COLREGs-compliance are taken into account. Special attention has been paid to situational awareness and risk assessment, particularly when the target ship is in breach of the COLREGs rules defined by the International Maritime Organisation. In order to implement COLREGs, the rules together with physical constraints are formulated as mathematical inequalities. A multiobjective optimization problem based on particle swarm optimization is then solved, the solution of which represents a newly-generated path. It is shown through simulations that the proposed method is able to generate COLREGs-compliant and collision-free paths even for non-cooperative targets i.e. vessels that are in breach of COLREGs.